N-Alkyl-Substituted Isatins Enhance P2X7 Receptor-Induced Interleukin-1β Release from Murine Macrophages - Ronald Sluyter; Kara L. Vine (Hindawi Limited, 2016)
Extracellular adenosine 5'-triphosphate (ATP) activates the P2X7 receptor channel to induce the rapid release of the proinflammatory cytokine, interleukin- (IL-) 1β, from macrophages. Microtubule rearrangements are thought to be involved in this process. Some isatin derivatives alter microtubules and display anticancer activities. The current study investigated the effect of isatin and seven structurally diverse isatin derivatives on P2X7-mediated IL-1β release from murine J774 macrophages. ATP-induced IL-1β and lactate dehydrogenase (LDH) release were assessed by specific colorimetric assays. P2X7 activity was determined by flow cytometric measurements of ATP-induced cation dye uptake. Cytotoxicity of isatin derivatives was determined using a tetrazolium-based colorimetric assay. ATP caused rapid IL-1β release in a concentration-dependent manner, and this process was completely impaired by the P2X7 antagonist, AZ10606120. In contrast, 5,7-dibromo-N-(p-methoxybenzyl)isatin (NAI) and 3-{4-[5,7-dibromo-1-(4-methoxybenzyl)-2-oxoindolin-3-ylidenamino]phenyl}propanoic acid (NAI-imine) enhanced P2X7-induced IL-1β release by twofold compared to that of isatin and the parent molecule, 5,7-dibromoisatin. NAI and NAI-imine had minimal effect on P2X7-induced dye uptake and LDH release. In contrast, 24-hour incubation with NAI and NAI-imine (in the absence of exogenous ATP) induced macrophage death in a concentration-dependent manner. In conclusion, this study demonstrates that N-alkyl-substituted isatins enhance P2X7 receptor-induced IL-1β release from murine macrophages. Thus, in addition to direct anticancer effects, these compounds may also impact inflammatory and immune cells within the tumor microenvironment.